PERANCANGAN GAME FLIGHT SIMULATOR N219 YANG DIKENDALIKAN DENGAN PERANGKAT SMARTPHONE ANDROID MELALUI MEDIA WI- FI - Ariska Hidayat; Bangga Dirgantara Adiputra (Compiler, 2015)
Flight simulation games are generally played on a smartphone or desktop computer. But still there is rarely flight simulation game that combines these two devices simultaneously with each other in a game. Software on a desktop computer that was developed in this research is to fly a plane from take off to landing at controlled by android smartphones using the accelerometer and touch sensors. The aircraft used for flight simulation games are made by PT. Digantara Indonesia, N219. The result of this design is only intended as a study course.